1989
DOI: 10.1152/ajpendo.1989.257.2.e127
|View full text |Cite
|
Sign up to set email alerts
|

Plasma membrane-specific deficiency in cardiac beta-adrenergic receptor in streptozocin-diabetic rats

Abstract: Cell surface [3H]CGP 12177 binding sites in 10-wk streptozocin-diabetic rats decreased by 41% (P less than 0.01) compared with that in the control rats. In contrast, there was no difference in the total cell receptor concentration between the control and the diabetic rats, which was measured by hydrophobic antagonist [125I]-iodocyanopindolol binding. Forty-eight-hour in vivo insulin treatment significantly (P less than 0.05) increased cell surface beta-adrenergic receptor concentration by 37% above that in dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…β-Adrenergic receptors are internalised during agonist stimulation and some pathological situations (Kashiwagi et al 1989;Bünemann et al 1999). Trafficking of receptors must therefore be avoided during tissue preparation to obtain information of cell surface receptor density.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…β-Adrenergic receptors are internalised during agonist stimulation and some pathological situations (Kashiwagi et al 1989;Bünemann et al 1999). Trafficking of receptors must therefore be avoided during tissue preparation to obtain information of cell surface receptor density.…”
Section: Discussionmentioning
confidence: 99%
“…After the incubation, biopsies were washed briefly and incubated for 10 or 60 min in buffer with 10 mU/ml insulin (filled triangles). Control muscles (open circles) remained in control buffer and some muscles were incubated with 10 µM isoprenaline during the whole period (filled circles) (n=5 for 10 min, otherwise 8-12) stimulation, as much as 70-80% of the receptors are internalised in the heart (Kashiwagi et al 1989). The physiological significance of the difference in internalisation of β-adrenergic receptors in types-I and -II muscle fibres remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These include changes of acetylcholine receptor number or affinity and sensitivity to cholinomimetics of several tissues (Latifpour et al, 1989;Carrier & Aronstam, 1987;Aronstam & Carrier, 1989). There are also marked alterations of peripheral catecholamine receptor function or sensitivity in vascular and nonvascular smooth muscle, including changes of x-adrenoceptor (Wald et al, 1988;Drukarch et al, 1989) and P-adrenoceptor mediated responses (Ingebretsen et al, 1983;Berlin et al, 1986;Ramanadhan & Tenner, 1987;Kashiwagi et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…Previous results [16] demonstrated that STZ-induced diabetes decreases by 50% the density of ␤-adrenergic receptors in rat prostatic membranes, in accordance with the important loss of functional response observed in the present work. A diminished ␤-adrenergic receptor density has also been found in other tissues from experimental diabetic rats such as heart [29], and this was partially ascribed to a possible abnormality in receptor recycling [30]. This possibility has not been analyzed in the diabetic rat prostate.…”
Section: Discussionmentioning
confidence: 99%